The Effect of Enviromental Uncertainty and Tax Avoidance: The Role of Managerial Ability in Emerging Country - Hanny Purnomo; Rizky Eriandani (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2023)
Taxes play an essential role in state funding. As something that is not profitable for the company, it usually encourages efforts to reduce taxes by doing a tax avoidance. This study aims to determine the effect of environmental uncertainty on tax avoidance and to determine the managerial ability to weaken the effect of environmental uncertainty on tax avoidance. This study using SPSS, 458 samples used in this study are manufacturing companies listed on the Indonesia Stock Exchange in the period 2016 – 2020. The results of this study indicate that environmental uncertainty affects tax avoidance and managerial ability strengthens the effect of environmental uncertainty on tax avoidance. The result may be due to the large influence of environmental uncertainty in the company so that the risks obtained are difficult for managers to overcome.